2010
DOI: 10.1152/japplphysiol.00460.2010
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation in multiple sclerosis

Abstract: Davis SL, Wilson TE, White AT, Frohman EM. Thermoregulation in multiple sclerosis. J Appl Physiol 109: 1531-1537. First published July 29, 2010 doi:10.1152/japplphysiol.00460.2010.-Multiple sclerosis (MS) is a progressive neurological disorder that disrupts axonal myelin in the central nervous system. Demyelination produces alterations in saltatory conduction, slowed conduction velocity, and a predisposition to conduction block. An estimated 60 -80% of MS patients experience temporary worsening of clinical si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(161 citation statements)
references
References 82 publications
4
155
0
2
Order By: Relevance
“…In addition, putative mechanisms underlying the effect of temperature on cognition remain to be explored in future research. That is, separate lines of research have shown that increased temperature is associated with increased lesion activity 3 and slowed or blocked conduction within demyelinated axons (for review, see 12 ), but it remains unclear whether these mechanisms or an as-yet unidentified mechanism is responsible for the heatrelated decrements in cognitive status observed among patients with MS in the current study. It may also be useful to examine individuals with secondary progressive MS, as we may expect to see exaggerated effects of slowed/blocked conduction as a result of demyelination in this more advanced disease subtype.…”
Section: Statistical Analysesmentioning
confidence: 86%
“…In addition, putative mechanisms underlying the effect of temperature on cognition remain to be explored in future research. That is, separate lines of research have shown that increased temperature is associated with increased lesion activity 3 and slowed or blocked conduction within demyelinated axons (for review, see 12 ), but it remains unclear whether these mechanisms or an as-yet unidentified mechanism is responsible for the heatrelated decrements in cognitive status observed among patients with MS in the current study. It may also be useful to examine individuals with secondary progressive MS, as we may expect to see exaggerated effects of slowed/blocked conduction as a result of demyelination in this more advanced disease subtype.…”
Section: Statistical Analysesmentioning
confidence: 86%
“…K+) ion channels in temperature transduction. In the context of human pathophysiology, increasing the knowledge on the function and interaction between TRP and K+ ion channels is of clinical significance for the study of those demyelinating diseases, amongst which multiple sclerosis, which present changes in membrane excitability and potassium channels function within the central nervous system (93), along with characteristics mechanisms of heat sensitivity resulting in temporary worsening of clinical symptoms (82,281).…”
Section: Warmth Transductionmentioning
confidence: 99%
“…For instance, after sympathectomy, local sweating responses to pilocarpine becomes exacerbated, but it subsequently decreases and, in some cases, ceases completely 22 . Decreased pharmacologically induced sweat production observed in type 1 diabetes and multiple sclerosis is an early sign of neuropathy, and it has been associated with reduced sympathetic nerve fiber density in the sweat glands 10,23,24 . In NF1, the development of large cutaneous and subcutaneous neurofibromas may cause dysfunctions in peripheral nerves leading to chronic pain, sensory loss, weakness or even palsy.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, the neuropathy caused by progressive central demyelization in multiple sclerosis produces systemic failure in maintaining internal temperature during heat exposure due to decreased neural control of cardiovascular responses and impaired sweat function. As a result, most multiple sclerosis patients experience transient and temporary worsening of clinical signs and neurological symptoms during exposure to higher environmental temperatures and exercise 10 . Additionally, exercise intolerance and sweating dysfunction are considered common manifestations of diabetic autonomic neuropathy, even in the early stages of this disease, once the sweating response is diminished or completely suppressed, especially in lower limbs 11,12 .…”
mentioning
confidence: 99%